2012
DOI: 10.1016/j.bmcl.2012.05.075
|View full text |Cite
|
Sign up to set email alerts
|

6β-N-Heterocyclic substituted naltrexamine derivative NAP as a potential lead to develop peripheral mu opioid receptor selective antagonists

Abstract: A 6β-N-heterocyclic substituted naltrexamine derivative, NAP, was proposed as a peripheral mu opioid receptor (MOR) selective antagonist based on the in vitro and in vivo pharmacological and pharmacokinetic studies. To further validate this notion, several functional assays were carried out to fully characterize this compound. In the charcoal gavage and intestinal motility assay in morphine-pelleted mice, when administered 0.3 mg/kg or higher doses up to 3 mg/kg subcutaneously, NAP significantly increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…1316 Briefly, NAP behaved as a low efficacy MOR partial agonist in the [ 35 S]GTP γ S binding assay whereas it also competitively inhibited MOR full agonist [D-Ala 2 -MePhe 4 -Gly(ol) 5 ]enkephalin (DAMGO)-stimulated [ 35 S]GTP γ S binding. 13, 15 Interestingly, NAP produced no apparent analgesic effects at doses up to 100 mg/kg, while it could antagonize the antinociceptive effect of morphine in the warm water tail-immersion assay with moderate potency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1316 Briefly, NAP behaved as a low efficacy MOR partial agonist in the [ 35 S]GTP γ S binding assay whereas it also competitively inhibited MOR full agonist [D-Ala 2 -MePhe 4 -Gly(ol) 5 ]enkephalin (DAMGO)-stimulated [ 35 S]GTP γ S binding. 13, 15 Interestingly, NAP produced no apparent analgesic effects at doses up to 100 mg/kg, while it could antagonize the antinociceptive effect of morphine in the warm water tail-immersion assay with moderate potency.…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, being a P-glycoprotein substrate, NAP has limited access to the central nervous system and dose-dependently restored morphine-impaired intestinal motility without precipitating significant withdrawal symptoms (jumps, wet-dog shakes, or locomotion). 14, 16 While originally NAP was defined as a potent antagonist on the MOR due to its lack of efficacy from our in vivo studies, its partial agonism on the MOR from the in vitro experiment results really intrigued us. Inspired and encouraged by these results and the aforementioned “proof-of-concept” in development of the G protein-biased MOR agonist TRV130, and based on the concept of biased antagonism, we hypothesized that NAP would act as a neutral antagonist for β-arrestin2 recruitment and low efficacy partial agonist for G-protein activation.…”
Section: Introductionmentioning
confidence: 99%
“…However, its therapeutic potential lies in its ability to antagonize MOR full agonist-induced intracellular calcium flux and β-arrestin2 recruitment (Zhang et al ., 2016). NAP dose-dependently restored the morphine-impaired intestinal motility without precipitating significant withdrawal of symptoms and thus held great promise in the treatment of opioid-induced constipation (Yuan et al ., 2012) (Table 1). In addition to multiple GPCRs as aforementioned, we summarize recent advances on serotonin 5-HT 2B receptor-and arginine-vasopressin V2 receptor-mediated biased signaling and highlight some biased ligands in Table 1.…”
Section: Biased Signaling On Selected Gpcrsmentioning
confidence: 99%
“…6 However, MNTX suffers from low activity at producing spontaneous bowel movements and prolonged use of Alvimopan increases the risk of myocardial infarction. 7 Therefore, the development of peripherally selective MOR antagonists would be of great benefit to patients suffering from OIC. Such compounds will also aid in further elucidating the role of MORs in OIC and other gastrointestinal neuropathies.…”
Section: Introductionmentioning
confidence: 99%
“…7 Further studies in the pharmacology of NAP demonstrated that it has mixed partial agonist and antagonist activity, with a bias towards antagonism of the β-arrestin2 pathway. 8 Given these promising results we sought to improve the peripheral selectivity of NAP via structural modifications and examine the pharmacology of the new derivative.…”
Section: Introductionmentioning
confidence: 99%